Root, shoot and leaf traits of the congeneric Styrax species may explain their distribution patterns in the cerrado sensu lato areas in Brazil - Habermann, Gustavo [UNESP]; Bressan, Anna C. G. [UNESP] (CSIRO Publishing, 2011)
Shoot and root lengths, the number of leaves, biomass and leaf area were measured in Styrax ferrugineus Nees and Mart., Styrax camporum Pohl. and Styrax pohlii A. DC cultivated in rhizotrons. Additionally, young individuals of these species were planted in a cerrado sensu stricto (s. str.), at the edge and in the understorey of a cerradao, and in the understorey of a riparian forest. Six months after planting, the specific leaf area (SLA) and the CO(2) assimilation rate were assessed on an area (A(area)) and mass (A(mass)) basis. S. ferrugineus exhibited greater root and lower shoot length in comparison to S. pohlii. The high shoot growth and concomitantly substantial root length of S. camporum may illustrate why this species is widely distributed in the cerrado sensu lato areas, whereas the deep roots of S. ferrugineus could account for its occurrence in the cerrado s. str. In the field, an irradiance-diminishing gradient enlarged the SLA of S. pohlii, which positively influenced its A(mass), and which could partially explain its occurrence in shady habitats. However, a non-plastic trait, such as the high shoot length of S. pohlii, is more likely to be responsible for the success of this species in forest habitats.
Keywords: Brazilian savanna; leaf gas exchange; photosynthetic capacity; Styracaceae; wet season